Entrepreneurial intention as a predictor of anxiety in university students in northern Peru - Musayon, Oscar Eden Guevara; Peri, Luis Alberto Vicuña; Loza, Miryam Griselda Lora (Edelweiss Applied Science and Technology, 2025)
The purpose of this research was to establish the extent to which the variable of entrepreneurial intention can predict anxiety levels among a group of university students in northern Peru. A quantitative approach was chosen, following a post-positivist paradigm, with a non-experimental and cross-sectional design, establishing a correlational-causal level. The sample consisted of 240 participants. The entrepreneurial intention questionnaire by Rueda et al. [1] and the Generalized Anxiety Scale GAD-7 by Spitzer et al. [2] were used. The results show a significant negative correlation between entrepreneurial intention and anxiety (Rho = -0.421, p < 0.01). The logistic regression model indicates that entrepreneurial intention explains 5.5% of the variability in anxiety (Nagelkerke R² = 0.055, p < 0.01), with a predictive effect confirmed by the Chi-square test (24.69, p < 0.001). Additionally, 87.9% of students exhibit high entrepreneurial intention, while 68.3% report anxiety, primarily mild (36.7%). It is concluded that entrepreneurial intention can act as a protective mechanism against anxiety in uncertain environments. These findings highlight the importance of strengthening entrepreneurial training programs, aligned with SDG 3 (Good Health and Well-being) and SDG 4 (Quality Education), to improve mental health and youth employability.